ANALISIS PUTARAN MESIN DIESEL 16 SILINDER MENGGUNAKAN ALAT DYNAMOMETER TERHADAP TORSI MESIN, DAYA MESIN DAN KOMSUMSI BAHAN BAKAR - Ahmad Yani (LPPM Universitas Bina Bangsa, 2022)
The diesel engine is a machine that converts heat energy directly into mechanical energy. In a four-stroke diesel engine, the working principle is to complete one cycle or a series of work processes to produce combustion, and one stroke of effort requires four strokes of the piston. This study aims to determine engine torque, engine power and fuel consumption in a 16-cylinder diesel engine. This research method was carried out experimentally by taking data using a dynamometer to obtain torque and engine power values. The results showed that each change in engine speed can affect the value of engine torque, engine power value and the amount of fuel consumption. This is because the higher the engine speed, the more combustion that will produce power than the engine itself, because the engine is a 4-stroke diesel engine, so every two rotations of the engine will produce one business step that will rotate the flywheel. The highest engine torque occurs at 1500 rpm with a value of 6061.161 lbft and the highest engine power occurs at 1800 rpm with a value of 1,861,691 HP, this happens because it is protection from the engine itself that is set by the manufacturer. While the highest fuel consumption occurs at 1900 rpm engine speed with a value of 0.354 lb/hp-hr